IMPROOVING THE ABILITY OF MOTHER LANGUAGE PRONUNCIATION IN MILD DOWN SYNDROME CHILDREN - Bayu Islam Assasaki (LPPM Universitas Dhyana Pura, 2016)
ABSTRACT The importance of communication could not be rejected for all of human being. Theimportant of communication skill was also required Down Syndrome children. Therefore this study would observed the pronunciation problem in mother language for children with MildDow Syndrome. The method of this study covered data source which was taken from children with Mild Down Syndrome 8 to 10 years old, data collection which was obtainedfrom investigated the children nad the data was analyzed buy identifying the pronunciationproblem and applied the intensive teaching method to solve it. Key Words: Mild Down Syndrome, pronunciation problem and intensive Teaching Method. ABSTRAK Pentingnya komunikasi tidak bisa dipungkiri oleh semua manusia. Pentingnya keterampilan komunikasi juga diperlukan oleh anak penderita Down Syndrome. Oleh karena itu penelitianini akan mengamati masalah pengucapan bahasa ibu bagi anak-anak dengan Mild Down Sindrom. Sumber data diambil dari anak-anak dengan Mild Down Sindrom berusia 8 sampai10 tahun, pengumpulan data yang diperoleh dianalisis dengan mengidentifikasi masalah pengucapan dan menerapkan metode pengajaran yang intensif untuk mengatasi masalahtersebut. Kata kunci: Mild Down Sindrom, masalah pengucapan dan metode pengajaran intensif